Analysis of statistics and anomalies of rainfall in Iran during the Warm period(1951-2010) - hosseinali roohbakhsh sigaroodi; mostafa karampoor; hooshang ghaemi; mohammad moradi; majid azadi (تحقیقات کاربردی علوم جغرافیایی)
Investigating the variability of the spatial-temporal pattern of rainfall, which can lead to climate change, due to its strong impact, is of interest to various scientists. For this purpose, after receiving the daily precipitation data of 27 stations for the period of 60 years (2010-1951), its quality and the total monthly precipitation and statistics necessary for the continuation of the research process such as mean, coefficient of variation, skewness, probability estimate of 20% The upper limit of the maximum and minimum rainfall average were calculated experimentally for a period of 60 years and two 30-year periods (1951-1980 and 1981-2010) and two periods of 10 years (1951-1960 and 2010-2001) for each of the spring and summer seasons Was calculated. The studies show relatively modest variations in spring and summer precipitation patterns on the Caspian coast, Northwest-West, 30 and 10 years old, compared to the 60-year, 30-year, and 10-year periods. In general, the mean of precipitation decreases from north and northwest to south and south east and increases the amount of coefficient of change and skidding. Except for the Caspian Basin, in the remaining stations, the average spring precipitation is higher than the average summer rainfall. There is a clear difference in the long-term characteristics of precipitation and its changes. It is worth mentioning that the increase in the coefficient of variation of the 30-year and 10-year periods is comparable to the corresponding periods at all stations, which indicates a decrease in the monthly and seasonal mean of spring and summer precipitation, which confirms the results of the decade and the first decade of the second decade. The greatest decrease occurred in the northern and western parts. In the second 30 years, the incidence of dry sunshine and drought-affected stations has increased. Therefore, it confirms the climate change for the Caspian and the Southwest coast.